EXPLORING SYNTAX VARIATIONS IN BILINGUAL CODE-SWITCHING: AN ANALYSIS OF ENGLISH-MIXED STRUCTURES - Zuhra, Rana May; Maharani, Puspita; Wulandari, Rahayu; Faiz, Muhammad; Salsabila, Hawa Alfina; Ismahani, Siti (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2024)
This study explores syntactic variations in bilingual code-switching, focusing on Englishmixed structures. Code-switching, the shift between two languages within a single conversation or discourse, frequently occurs in multilingual settings and can be influenced by various linguistic and social factors. The aim of this research is to analyze patterns and syntactic structures in sentences containing a mixture of English and another language, revealing how simultaneous use of two languages creates unique sentence structures. Using a qualitative approach with in-depth interviews, the study involved 10 bilingual respondents who actively use English alongside their native language in daily conversations. The interview data were analyzed thematically to identify common patterns in syntactic code-switching, such as word order, pronoun usage, and phrase structure differences. Findings indicate that code-switching occurs not only at the lexical level but also at the syntactic level, with significant variations in sentence structures influenced by grammatical differences between English and the native language. The study reveals that factors like conversational context, social setting, and language proficiency level also influence syntactic forms in code-switching. The implications of this study provide new insights into how grammatical rules from two different languages can interact and adapt, enriching our understanding of language adaptability among bilingual speakers. These findings contribute to applied linguistics and can be applied in language education as well as cross-cultural communication studies.